Early Post-operative Outcomes of Single versus Multiple Arterial Grafts in Coronary Artery Bypass Grafting; A Comparative Analysis - Chaudhry, Imtiaz Ahmed; Ali, Nasir; Afzal, Sidra; Bashir, Imran (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare early post-operative outcomes of Single versus Multiple Arterial grafts in Coronary Artery Bypass Grafting (CABG) surgery.Study Design: Analytical Cross-sectional study.Place and Duration of Study: Adult Cardiac Surgery, Armed Forces Institute of Cardiology/National Institute of Heart Diseases Rawalpindi Pakistan, from Jul 2022 to May 2023.Methodology: One hundred and forty nine patients planned for elective isolated CABG (with two or more grafts) were enrolled in study using consecutive sampling. They were allocated into two groups, group A (Multiple Arterial CABG group) and group B (Conventional CABG group). Data was collected on early post-op outcomes i.e. ICU stay, ventilation time, inotropic duration, chest drainage, rhythm complications including Supraventricular Tachycardia (SVT) and mortality using a structured proforma. Chi-square and t-test were applied to make comparison between both groups. p